2000
DOI: 10.1054/bjoc.1999.1006
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of P73 and TP53 in Merkel cell carcinoma

Abstract: SummaryThe p73 gene has been mapped to 1p36.33, a region which is frequently deleted in a wide variety of neoplasms including tumours of neuroectodermal origin. The p73 protein shows structural and functional homology to p53. For these reasons, p73 was considered as a positional and functional candidate tumour suppressor gene. Thus far, mutation analysis has provided no evidence for involvement of p73 in oligodendrogliomas, lung carcinoma, oesophageal carcinoma, prostatic carcinoma and hepatocellular carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…16 Moreover, UV-associated mutations in the tumor suppressor p53 have been documented in some cases of Merkel cell carcinoma. 63,64 Increased P53 protein detection seems to be more commonly found in Merkel cell polyomavirus- negative tumors. 4,5 Similarly, pure squamous cell carcinoma, a tumor known to express P53, and thought to be pathogenetically related to p53 alterations, is the archetypal UV-related cutaneous carcinoma, and for the most part, does not express Merkel cell polyomavirus.…”
Section: Discussionmentioning
confidence: 97%
“…16 Moreover, UV-associated mutations in the tumor suppressor p53 have been documented in some cases of Merkel cell carcinoma. 63,64 Increased P53 protein detection seems to be more commonly found in Merkel cell polyomavirus- negative tumors. 4,5 Similarly, pure squamous cell carcinoma, a tumor known to express P53, and thought to be pathogenetically related to p53 alterations, is the archetypal UV-related cutaneous carcinoma, and for the most part, does not express Merkel cell polyomavirus.…”
Section: Discussionmentioning
confidence: 97%
“…For example, there is evidence that the binding of T-antigen to p53 in SV40 may not be sufficient to block p53 function and that other indirect mechanisms (involving small T-antigen and/or the J- and Rb-binding domains of the LT-antigen) are also important in functional suppression of p53 [52, 53]. Consistent with MCPyV somehow disabling p53 function in MCC tumors, inactivating mutations in TP53 gene and/or overexpression of p53 have been seen only in a small subset of MCC tumors [54, 55]. Moreover, recent studies have indicated an inverse relationship between p53 expression and MCPyV viral abundance in MCC tumors as well as p53 overexpression potentially being associated with poor outcome [56, 57].…”
Section: Role Of Mcpyv In Pathogenesis Of MCCmentioning
confidence: 99%
“…Furthermore, the authors noted that this change might also result from increased awareness and reporting of MCC [18]. A further risk factor for MCC is UVB exposure, as shown in epidemiological studies [23] and mutations analysis of TP53 [24]. Expression of p53 has been correlated to MCV-negative MCC [13, 14, 25], thus suggesting a different pathogenesis in MCV-positive and MCV-negative MCC.…”
Section: Introductionmentioning
confidence: 99%